An improved energy management control strategy for a standalone solar photovoltaic/battery system - Ouadiâ Chekira; Ali Boharb; Younes Boujoudar; Hassan El Moussaoui; Tijani Lamhamdi; Hassane El Markhi (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This paper proposes efficient energy management in hybrid microgrid-comprising of photovoltaic (PV) and battery storage systems. The proposed technique. The hybrid system's power balance is based on smart control to meet the demands of isolated off-grid direct current (DC) loads as well as to stabilize the voltage to DC Bus. The Perturb and Observe technique (P&O) is used to achieve maximum power point tracking by adjusting the duty cycle of the Bidirectional converter, which links the Li-ion battery to the DC Bus of stand-alone power systems (SPS). The proposed controller regulates the power flow of the battery for efficiency voltage control in a microgrid. The energy management system proposed has been approved using MATLAB/Simulink under variable solar irradiation conditions. The simulation results show that the technique used increases the battery cycle-life and better energy management and voltage control performance compared with previous examples.